Effect of moderate-intensity continuous training and high-intensity interval training with astaxanthin supplementation on inflammatory factors of cardiac tissue in type 2 diabetic rats - Tohid Azizzadeh; Mohammad Reza Zolfaghari; Amir Fattahi; Kamal Khademvatani (فصلنامه ابن سینا)
Background and aims: The prevalence of diabetes has made necessary changes in lifestyle to prevent its complications. In this study, the effect of moderate-intensity continuous training (MICT) and high-intensity interval training (HIIT) with staxanthin supplementation on inflammatory biomarkers in the cardiac tissue of diabetic rats was investigated. Methods: In this study, 42 male rats (age six weeks), after induction of type 2 diabetes,were randomly divided into seven groups (six in each group): 1)diabetic control; 2) diabetic Sham; 3) diabetes+supplement; 4) diabetes+HIIT; 5) diabetes+HIIT+supplement; 6) diabetes+MICT; and 7) diabetes+MICT+supplement. The HIIT groups ran with an intensity of 80% VO2max, and MICT groups ran with an intensity of about 65% to 75% VO2max on the treadmill (five sessions per week for eight weeks). The supplement was taken daily at a dose of 3 mg per kg. The cardiac tissue was removed 24h after the last training session (night fasting). Inflammatory biomarkers (IL-1b, IL-6, TNF-α, and CRP) of the cardiac tissue were measured by Western blotting. Results: After eight weeks of training, inflammatory biomarkers showed a significant decrease compared to the control group (p<0.05), and no significant changes were observed in the supplement group. Conclusion: Due to the effect of MICT and HIIT in reducing inflammatory biomarkers, it can be used as a therapeutic strategy. It seems that the MICT with supplements may have more effective in these patients, while supplements alone have no effect on inflammatory markers.